2019
DOI: 10.3390/s19040908
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Based Methods for Measuring Respiratory Rate

Abstract: There is an ever-growing demand for measuring respiratory variables during a variety of applications, including monitoring in clinical and occupational settings, and during sporting activities and exercise. Special attention is devoted to the monitoring of respiratory rate because it is a vital sign, which responds to a variety of stressors. There are different methods for measuring respiratory rate, which can be classed as contact-based or contactless. The present paper provides an overview of the currently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
257
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(268 citation statements)
references
References 250 publications
3
257
0
8
Order By: Relevance
“…Besides ECG and PPG based methods, several additional concepts of estimating respiratory parameters have emerged. Other approaches used to estimate respiratory signals include respiratory sounds, breathing air temperature, humidity and components [37], the oscillometric cuff pressure, Korotkoff sounds, as well as the seismocardiogram (SCG) [38]. For the latter, it has been shown that the morphology of the vibrational cardiac waveforms varies with the respiratory volume [39,40], and methods of extracting respiratory phases [41,42], effort [43] and breathing states such as normal, breathless, long, and labored [44] have been proposed.…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…Besides ECG and PPG based methods, several additional concepts of estimating respiratory parameters have emerged. Other approaches used to estimate respiratory signals include respiratory sounds, breathing air temperature, humidity and components [37], the oscillometric cuff pressure, Korotkoff sounds, as well as the seismocardiogram (SCG) [38]. For the latter, it has been shown that the morphology of the vibrational cardiac waveforms varies with the respiratory volume [39,40], and methods of extracting respiratory phases [41,42], effort [43] and breathing states such as normal, breathless, long, and labored [44] have been proposed.…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…The generally accepted clinical standard for heart rate monitoring using devices is the use of ECG monitoring [12] or pulse frequency from a photoplethysmogram [13]. Respiratory rate monitoring in patients requiring continuous monitoring is typically performed via thoracic bioimpedance from ECG leads or capnography [14]. Blood pressure monitoring in clinical spaces is typically performed via an automated oscillometric cuff [15], while oxygen saturation monitoring is performed using a two-wavelength pulse oximeter, either as a standalone device or integrated into a vital signs monitor [16].…”
Section: Rationalementioning
confidence: 99%
“…Pulse oximetry, while now present in most smartphones [18] continues to rely on the same principle of the change in the absorbance of visible and infrared light of hemoglobin at different oxygen saturations [16]. Recent incremental innovations to other vital signs monitoring include new algorithms to better detect heart rate and respiratory rate [14] or the combination of multiple measurement devices into a single, more portable unit [19].…”
Section: Rationalementioning
confidence: 99%
“…In general, the main inconveniences are related to the correct and specific use of each contact sensor, the stress, pain, and irritation caused, mainly on some vulnerable skins, like neonates and burns patients [1]. For a review of contact-based methods and comparisons see [2]. Contactless breathing monitoring is a recent research interest for clinical and day-to-day applications; a review, and comparison of contactless monitoring techniques can be seen in [3].…”
Section: Introductionmentioning
confidence: 99%